Wienerbröd och andra finesser. Den nya svensk-litauiska ordboken - Sausverde, Erika (Nordiske Studier i Leksikografi, 2004)
The paper presents a new Swedish-Lithuanian dictionary (about 28,500 words) based on Swedish Lexin series. It presents a short survey of the Swedish-Lithuanian lexicographical situation, the background to the project, peculiarities and difficulties that we were confronted with while preparing the dictionary, with special attention to semantics and the problem of equivalents. The problems are typical in lexicography when compiling bilingual dictionaries and are based on different historical, cultural, social, etc. conditions of the two language regions.